Risk and Financial Consequences - Halkos, George (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Twenty interesting studies on, among others, risks towards firm performance, financial risk and financial uncertainties, risk consequences for European countries' businesses and economies from the Russia and Ukraine conflict, the effects of adopting enterprise risk management on the performance and risks of European publicly listed insurance firms, the management of financial risks while performing international commercial transactions, market liquidity and its dimensions, benchmarking as a way of finding risk factors in business performance, the effect of risk disclosure for trade credit, risk perception, accounting, and resilience in public sector organizations, and psychological effects from potential unexpected environmental disasters on investors. Although disasters are associated with risk, investors tend to have a different perspective depending on the source of the disaster. More specifically, if a country is facing a natural disaster, where no one can be blamed, the foreign investors who may hold a country's bonds will continue to trust the country due to the "innocence" of the country. On the other hand, when a firm causes a technological disaster, such as a nuclear power plant explosion, investors, if this corporation is publicly traded, will "punish" the firm by selling its shares at any price to avoid a bigger loss.